SELECTION OF PAYMENT METHODS IN ONLINE MARKETS USING ANALYTICAL HIERARCHICAL PROCESS - Refgiufi Patria Avrianto; Januponsa Dio Firizqi; Rido Dwi Kurniawan; Richardus Eko Indrajit; Erick Dazki (Informatika, Universitas Jenderal Soedirman, 2022)
Transactions through the online market are carried out using various payment transaction methods, both digitally and in cash through the Cash on Delivery (COD) service. Therefore, with various payment methods that exist in the process of buying and selling transactions on the online market, especially in payment transactions in the current digital 4.0 era. Often users feel confused about which payment method to use, because there are quite a lot of payment methods to choose from. This study aims to examine and analyze the choices of online market users in choosing payment methods (Digital Banking, ATM Transfer, Credit Card, E-Wallet, COD) when transacting. The analysis data was obtained by distributing questionnaires to active users of the online market which were then processed and tested using the Analytical Hierarchy Process (AHP) method with the help of the AHP Calculator application. The results of this study indicate that Digital Banking excels with a value percentage of 28.7%, followed by COD 20.7%, E-Wallet 20.4%, ATM Transfer 18.9% and the last is Credit Card 11.2%. In general, the main criteria that are prioritized in the selection of payment methods are trust with a weight value of 28.8% and the most prioritized alternative is using Digital Banking with a value of 28.7%. In addition, it is also known that the AHP method is very suitable for use in the decision-making process with multi-criteria and multi-alternatives, as well as decisions in choosing a payment method, because this method shows the results of a weighting comparison between criteria and alternatives.